"Woe unto us": divine wrath and godly sorrow in an English plague sermon (1637). Issue 3 (4th May 2022) - Formby, Olivia
ABSTRACT: The historiography of early modern plague assumes that early modern emotions mirrored the volatile fearfulness dramatised in contemporary English plague literature, and that there was no comfort to be found in its reformative message. Meanwhile, historians have struggled to explain the resilience of English communities through frequent epidemics. Using the case study of a 1637–8 epidemic in Kingston upon Hull, where the preacher Andrew Marvell (c. 1584–1641) was broken from quarantine to return to his pulpit, this article contests that the persistence of sermons in plague provided a vital point of pastoral continuity, as well as a tool for emotional resilience. A close reading of Marvell's surviving manuscript plague sermon, delivered at the funeral of a plague victim, will demonstrate how narratives of divine wrath and godly sorrow, embedded within early modern print culture, could offer emotional direction and succour in practice.